(untitled) (Research, Society and Development, 2022)
Oral rehabilitation, through mucous-supported complete dentures or under implants, is an option to restore function and aesthetics to totally edentulous patients. Thus, the present study aimed to carry out a critical review of the literature with the main focus on evaluating the impact of oral rehabilitation on the quality of life of totally edentulous patients. After the search process, fourteen works were selected. Most studies aimed to assess the impact of oral rehabilitation on the quality of life of totally edentulous patients. For this review, literature searches were conducted in the following databases: Medline (Pubmed), Web of Science and Scopus, using the keywords “quality of life”, “mouth rehabilitation” and “edentulous mouth”. The results showed a significant improvement in the oral health-related quality of life of patients after complete denture rehabilitation. On the other hand, implant-supported complete denture rehabilitations showed better efficacy when compared with mucous-supported complete dentures. Therefore, restoring function and aesthetics through oral rehabilitation is of paramount importance to restore people’s quality of life.